Kerstin Droß-Krüpe (ed.). Textile trade and distribution in antiquity/Textilhandel und -distribution in der Antike - Russell, Ben (Journal of Greek Archaeology, 2016)
New scientific techniques, increasingly precise excavation strategies, and an upsurge in interest in the ancient economy—and in particular in identifying new datasets that might contribute to our understanding of it—mean that ancient textiles are finally receiving the attention they deserve. While research on ancient dress and textile production has a long history, it has tended to be something of a lonely one. Only in the past ten years have economic historians begun to appreciate the potential of this area, and only over the same period have textile specialists begun to explore how their work can inform debates in economic history.